A modified cyclone stickiness test for characterizing food powders - P. Intipunya (2018)
A cyclone stickiness test device from a preliminary work was modified and used for characterizing stickiness behaviour of food powders. This test device employed the principle of particle dynamics in cyclone section of a spray dryer. The device was more compacted and consisted of temperature-humidity controlled air generator and cyclone test chamber. Characteristic temperature-humidity curves were determined and served as the maximum test conditions. Skim milk powder was used as a model for stickiness testing. The sample was subjected to various air conditions in the cyclone and stickiness conditions were determined. Surface moisture content and glass transition temperature at sticky point were also analysed. It was found that as the particle surface temperature increased humidity at which stickiness occurred decreased. Stickiness curve was drawn to separate between sticky and non-sticky conditions. The curve of glass transition temperature vs equilibrium surface moisture content at sticky points was obtained. It was found that the sticky curve laid at 11.4 °C above the glass transition temperature line. © 2009 Elsevier Ltd.